Isoprostanes in wastewater of two Italian cities as a community-level metabolism linked to SARS-CoV-2 RNA and COVID-19 cases - Giulia Squillacioti; Samar El Sherbiny; Alex Affricano; Lisa Richiardi; Claudio Cassardo; Giulia Baldelli; Claudio Medana; Giorgio Brandi; Roberto Bono (BMC Public Health)
Abstract Wastewater-based Epidemiology (WBE) was initially employed as a valuable tool for monitoring pathogens. Nowadays, WBE has expanded its original focus to the quantification of several “community-level metabolism” indicators to complement Public Health monitoring campaigns. Recently, wastewater isoprostanes have been suggested as biological indicators of oxidative stress and community anxiety levels during the COVID-19 pandemic. However, previous studies were lacking of concomitant quantifications linking isoprostanes in sewage with COVID-19 pandemic indicators. This study provides an application case to expand the application of a WBE approach for the investigation of community-wide oxidative stress levels and COVID-19 disease. We quantified the occurrence of three oxidative stress biomarkers in wastewater samples collected from two Italian cities (study sites A and B) from January to December 2022. Among the selected oxidative stress biomarkers, only 8-isoprostaglandin F2α (8-iso-PGF2α) and 5-iso Prostaglandin F2α-VI (5-iPF2α-VI) were detectable, while prostaglandin E2 (PGE2) was undetectable during the entire study period in both sites. The annual trend of 8-iso-PGF2α mass load and SARS-CoV-2 concentration in sewage was significantly and moderately cross-correlated, as a at study site A (Spearman’s rho = 0.62) and study site B (Spearman’s rho = 0.68). The same findings were confirmed for the cross-correlations including 8-iso-PGF2α concentrations instead of per capita mass load. A moderate and significant cross-correlation with the annual trend of monthly average daily COVID-19 cases (Spearman’s rho = 0.67) was observed for one study site and with a time lag = 1. Our findings support the hypothesis that human biomonitoring, via the quantification of oxidative stress biomarkers in sewage, can be effectively used to investigate the emerging field of the community-level metabolism.